2002
DOI: 10.1002/1615-9861(200209)2:9<1204::aid-prot1204>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Duration of ischaemia determines matrix metalloproteinase-2 activation in the reperfused rabbit heart

Abstract: It has been hypothesised that activation of matrix metalloproteinase-2 (MMP-2) contributes to reversible myocardial dysfunction (stunning) following short-term ischaemia and reperfusion. Gelatin zymography was used to measure release of both pro-MMP-2 (72 kDa) and MMP-2 (62 kDa), into the coronary effluent from isolated, perfused rabbit hearts during 90 min aerobic perfusion (control), or low-flow ischaemia (15 or 60 min at 1 mL/min), followed by 60 min reperfusion. In controls, pro-MMP-2 was detected in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other authors (Prasan et al 2002) showed that there is an increase in the pro‐MMP–2 activity after 60 min of low‐flow ischaemia. However, they used low‐flow ischaemia, which induced a permanent washout of the metabolites and enzymes, including MMP–2.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors (Prasan et al 2002) showed that there is an increase in the pro‐MMP–2 activity after 60 min of low‐flow ischaemia. However, they used low‐flow ischaemia, which induced a permanent washout of the metabolites and enzymes, including MMP–2.…”
Section: Discussionmentioning
confidence: 95%
“…A possible limitation of our study is the different perfusion times used in the protocols. Perfusion of the hearts could mildly alter oxidative stress itself, modifying the activity of MMP-2 in a time-dependent way (18). However, the activity data of MMP-2 were accompanied by changes in dystrophin levels, which significantly decreased during ischemia when MMP-2 activity was increased.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 is known to be transiently activated by acute myocardial injury [8,[18][19][20][21][22]. Pharmacological inhibition or targeted deletion of the MMP-2 gene attenuates left ventricular dilation and contractile depression early after murine myocardial infarction [18].…”
Section: Discussionmentioning
confidence: 99%